2011
DOI: 10.2139/ssrn.941795
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure Provision and Macroeconomic Performance

Abstract: Behavioral di¤erences between economies where infrastructure is privately provided and where the government is the sole provider are examined in the context of a growing economy. The choice between private and public provision generates di¤erences in the private sector's ability to internalize capital utilization decisions and market prices along the equilibrium path. This in turn has a crucial impact on the e¤ects of …scal policy on resource allocation and welfare in each regime. If the government wants to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Furthermore, in a majority voting system whereby individuals vote for the size of the public education system, we show that all individuals agree on a tax level which is lower than the one which maximizes growth. In light of this result, a corollary is that there is no trade-off between growth and equity, that is, our framework shows that a higher level of growth and a lower level of inequality can be mutually compatible when the 4 Our framework can also be related to the literature on government versus private provision of public goods (see, e.g., Devarajan, Xie, and Zou 1998;Chatterjee and Morshed 2011). An important difference of these frameworks with ours, though, is that they do not consider either the possibility of parallel investments (public-private) which may interact with each other, or the issue of distribution.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, in a majority voting system whereby individuals vote for the size of the public education system, we show that all individuals agree on a tax level which is lower than the one which maximizes growth. In light of this result, a corollary is that there is no trade-off between growth and equity, that is, our framework shows that a higher level of growth and a lower level of inequality can be mutually compatible when the 4 Our framework can also be related to the literature on government versus private provision of public goods (see, e.g., Devarajan, Xie, and Zou 1998;Chatterjee and Morshed 2011). An important difference of these frameworks with ours, though, is that they do not consider either the possibility of parallel investments (public-private) which may interact with each other, or the issue of distribution.…”
Section: Introductionmentioning
confidence: 84%
“…Our framework can also be related to the literature on government versus private provision of public goods (see, e.g., Devarajan, Xie, and Zou ; Chatterjee and Morshed ). An important difference of these frameworks with ours, though, is that they do not consider either the possibility of parallel investments (public–private) which may interact with each other, or the issue of distribution.…”
mentioning
confidence: 99%
“…However, Rumbos and Auernheimer (2001), Dalgaard (2003), Monteiro et al (2013) and Chatterjee (2005) and Chatterjee and Morshed (2011) have clearly demonstrated that physical capital utilization is important for the dynamics of growth and convergence as well 2 . Now, if we take the results in this strand of literature seriously, the question arises: If physical capital utilization has long-run relevance, why should this not be the case for automation capital as well?…”
Section: Introductionmentioning
confidence: 99%